Multimodal neurocritical monitoring - Ming-Tao Yang (Biomedical Journal, 2020)
Neurocritical monitoring is important in caring for patients in the neurological intensive care unit. Although clinical neurologic examination is standard for neurocritical monitoring, changes found during the examination are often late signs and insufficient to detect and prevent secondary brain injury. Therefore, various neuromonitoring tools have been developed to monitor different physiologic parameters, such as cerebral oxygenation, cerebral blood flow, cerebral pressure, cerebral autoregulation, cerebral electric activity, and cerebral metabolism. In this review, we have discussed current commonly used neurocritical monitoring tools. No single monitor is sufficient and perfect for neurocritical monitoring. Multimodal neurocritical monitoring is the current trend. However, the lack of common formatting standards and uncertainty of improvement in patients’ outcomes warrant further studies of multimodal neurocritical monitoring. Nevertheless, multimodal neurocritical monitoring considers individual pathophysiological variations in patients or their injuries and allows clinicians to tailor individualized management decisions.